Step-by-step explanation
We have a line given by the following function:
![f(x)=(1)/(2)x+2.](https://img.qammunity.org/2023/formulas/mathematics/high-school/xy8tmhs308ggjg8czfxrnvagv3go4miopr.png)
The inverse function of f(x) is the function g(x), that satisfies:
![g(f(x))=x.](https://img.qammunity.org/2023/formulas/mathematics/high-school/rdkl40gx1s8j3v82vr3lrxr5wmf4h45c4j.png)
To find the inverse function, we replace x by y in the equation of f(x), and then we equal to x and solve for y, we get:
![\begin{gathered} x=f(y)=(1)/(2)y+2, \\ x-2=(1)/(2)y, \\ y=2*(x-2), \\ y=2x-4. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3dknxgx69nvcjml57x0pv1lx63q3cnodip.png)
So the inverse function is:
![g(x)=2x-4.](https://img.qammunity.org/2023/formulas/mathematics/high-school/nza8xm2kgfexdv4gfdymve8p4won7e2ao6.png)
Plotting f(x) and g(x), we get the following graph:
Comparing this graph with the options, we conclude that option A is the correct answer.
Answer
Graph A.